2016
DOI: 10.1002/pd.4838
|View full text |Cite
|
Sign up to set email alerts
|

Maternal 47,XX,i(X)(q10) as a cause of false positive sex chromosome aneuploidy in noninvasive prenatal screening

Abstract: What's Already Known About This Topic? Noninvasive prenatal screening (NIPS) has been shown to be a highly accurate tool for prenatal detection of aneuploidy, without risk to the fetus Less is the accuracy of NIPS for the detection of sex chromosome aneuploidies (SCAs) Reduced accuracy in diagnosis of SCA has been attributed to placental mosaicism It is probable that some false‐positive diagnoses of sex chromosome aneuploidy are because of abnormal maternal karyotype What Does This Study Add? This is a case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Yao et al [40] demonstrated for the first time that maternal genomic materials could affect NIPT accuracy. Afterward, many studies demonstrated that maternal factors could significantly affect the accuracy of NIPT for fetal SCAs [8, [16][17][18][19][20][21][22][23][24]41]. Wang et al [8] reported that maternal X chromosome aneuploidy and mosaicism were responsible for approximately 8.6% of discordant NIPT results for SCAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yao et al [40] demonstrated for the first time that maternal genomic materials could affect NIPT accuracy. Afterward, many studies demonstrated that maternal factors could significantly affect the accuracy of NIPT for fetal SCAs [8, [16][17][18][19][20][21][22][23][24]41]. Wang et al [8] reported that maternal X chromosome aneuploidy and mosaicism were responsible for approximately 8.6% of discordant NIPT results for SCAs.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [20] reported that SCA results were associated with the presence of maternal ChrX genetic anomalies in 21 cases (24.42%), which indicated that maternal SCA was an important cause for the false positivity of fetal SCAs by NIPT. De-Maio et al [41] presented a case of abnormal maternal karyotype 47,XX,i(X)(q10) showing false positivity for fetal SCA. In this study, our data showed that 12.34% of the false positivity in NIPT results was caused by maternal sex chromosome abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postnatal karyotype was 46, XX. Maternal karyotype was later performed and revealed 47, XX, i(X) (q10) (in addition to having two normal X chromosomes, the mother had an isochromosome for the long arm of the X chromosome, resulting in two additional copies of the long arm of the X chromosome) (Table ) (DeMaio et al, ).…”
Section: Discussionmentioning
confidence: 99%